Features for Discriminating Normal Cases in Mass Screening for Gastric Cancer with Double Contrast X-ray Images of Stomach - Abe, Koji; Nakagawa, Hidenori; Minami, Masahide; Tian, Haiyan (British Journal of Healthcare and Medical Research, 2015)
In a mass screening for gastric cancer, diagnosticians read many stomach X-ray pictures at a time. To decrease the number of reading the pictures in the mass screening, the proposed method discriminates normal cases in stomach X-ray images using the proposed features. In the normal cases, folds on the stomach wall appear in parallel in the images. Considering this characteristic, the proposed method measures parallelism of the folds in the images. Experimental results of the discriminations for 88 images where 13 abnormal cases are included have shown that the proposed features are well effective for recognizing normal cases.